Roles of different fertilizer management practices on mulberry leaf yield and quality - Ahmed, Faruque; Sultana, Rafia; Ahmed, Oli; Akhtaruzzaman, Md.; Iqbal, Md. Toufiq (International Journal of Agricultural and Biological Engineering, 2017)
Effects of fertilizer management practices on leaf yield and quality of mulberry plant are important for sustainable mulberry plant production. This study was undertaken to improve the growth, yield and biochemical contents in an instant available form in mulberry plant through different fertilizer management practices. There were four fertilizer management practices like control (CT), basal (BS), urea+magic growth (UM) and basal+urea+magic growth (BUM) were applied on mulberry plant (Morus SPP.). Results of this investigation revealed that among the various fertilizer treatments on the foliar application of (3 g urea + 3 mL magic growth) per liter water with BSRTI recommended BS of NPK performed well in respect of growth parameters and biochemical constituents. The highest 10 leaf area (638.64 cm2), leaf number per branch (50), total leaf weight per plant (785.64 g), node per meter (28.67), specific leaf weight (0.005817 g/cm2), length of longest shoot (173.25 cm) and total leaf yield per hectare per year (41 610 kg) were noticed in BUM treatment followed by UM, BS and CT treatments. Further the highest moisture (74.38%), moisture retention capacity (33.31%), total mineral (12.10%), total sugar (3.99%), reducing sugar (4.05%), crude protein (21.01%), starch (9.72%) and soluble carbohydrate (11.41%) were also recorded in BUM treatment as compare to UM, BS and CT treatments. The outcome of research implies that among the four fertilizer management practices foliar spray of (3 g urea + 3 mL magic growth) per liter water with BSRTI recommended BS dose of NPK performed well and successfully augments the productivity and biochemical constituents of mulberry plant. Keywords: liquid fertilizer, silkworm, foliar spray, photosynthesis, pruning DOI: 10.25165/j.ijabe.20171005.2268 Citation: Ahmed F, Sultana R, Ahmed O, Akhtaruzzaman M, Iqbal M T. Roles of different fertilizer management practices on mulberry leaf yield and quality. Int J Agric & Biol Eng, 2017; 10(5): 104–114.